Characterization of isolated mung bean starch from Green Pag-asa 7-Mg 11 (Kintab) and Yellow Pag-asa 3-Mg 03 (Ginintuan) mung bean Philippine cultivars (Vigna radiata(L.) Wilczek) - Uy, Abigail Joyce S. (College of Home Economics, University of the Philippines Diliman, 2019)
Mung bean (Vigna radiata (L.) Wilczek) starches from two Philippine cultivars, Pag-asa 3 Mg 03 (Ginintuan), and Pag-asa 7 Mg 11 (Kintab) were isolated by wet extraction process. The quality characterization of the starches involved analyses of physico-chemical properties (water activity [Aw], pH, and Apparent Amylose content), proximate composition, structural properties (Scanning Electron Microscope [SEM], Optical Microscopy), pasting behavior (Rapid Visco-Analyzer [RVA]), and thermal degradation (Differential Scanning Calorimetry [DSC]). The percentage flour yields for green mung bean (GMB) and yellow mung bean (YMB) cultivar were about 96% with corresponding low starch yields of (14-19%) (% w/w, dry-basis) respectively. Green mung bean flour (GMBF) and yellow mung bean flour (YMBF) were both classified as low acid, and low Aw with low apparent amylose content. The extracted starches from the mung bean flours (MBFs) were classified with high acidity, and low Aw with high apparent amylose content. The proximate profiles of the starches were similar, with values ranging for each component as follows: fat (0.2%), fiber (0.4%), and ash (0.1%). However, GMBS had higher moisture content, while YMBS had a higher protein and total carbohydrate content. The MBFs granules exhibited starch granules possibly adhering to or surrounded by other components such as cell wall, fat, and protein bodies. These also exhibited a Ctype Brabender viscosity profile, which presented a restricted granule swelling, no pasting peak, and a viscosity that plateaus. The MBSs granules had shapes ranging from 2 oval to round to kidney shape. The GMBS granules ranged from (10-25 μm) measured lengthwise. These exhibited A-type Brabender viscosity profiles that had high-swelling granule starches presenting viscosity patterns with high pasting viscosity. The YMBS granules ranged from (12-34 μm) measured lengthwise, also exhibiting A-type Brabender viscosity profiles that had high-swelling granule starches presenting viscosity patterns with high pasting viscosity. The results from the Optical Imaging then confirmed the general trend of starch types, shapes, and sizes from the SEM analysis. All DSC curves were endothermic with thermograms exhibiting dual peaks indicating that gelatinization of amylopectin happened in the first peak while the dissociation of the amylose-lipid complexes occurred in the second peak. It was recommended that an improvement in the starch isolation technique should be done to improve the % starch recovery. It was also recommended that the proximate analyses and the pasting property analysis be considered as quality determinants for the monitoring of the quality characteristics of mung bean flour and starch.